PERSONALITAS PRESIDEN NICHOLAS SARKOZY DAN KEBIJAKAN TERHADAP KAUM IMIGRAN DI PERANCIS - , GANES NIRWINA P.SARI, Rocdi Mohan Nazala, S.IP, MSA, M.Lit ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This undergraduate thesis examines the influence of personality of President Nicholas Sarkozy in restriction policy toward immigrants in France. This research proves that personality had significant influence in policy making by President. How family and education background, ideological and political orientation experienced and owned by president used to see how the personality is formed and influence the policy. Restriction policies towards immigrants in France by President Nicolas Sarkozy caused by his own personality. Personality identified immigrants as one of the main key. Since 2002, French immigration policy has been largely driven by Nicolas Sarkozy, as Minister of the Interior, leader of the centre-right UMP and, from 2007, as President of the Republic. His discourse and action on immigration control and integration have diverged in significant respects from earlier centre-right handling of these issues.